aalihasmith95
aalihasmith95
01-11-2015
Mathematics
contestada
6 [ 4 × ( 72 - 63 ) ÷ 3 ]
Respuesta :
Аноним
Аноним
01-11-2015
Do parenthesis first.
72 - 63 = 9, simplifies to:
6 [ 4 * (9) ÷ 3]
multiply 9 and 4, which is 36, divide that by 3, which equals, 12
6 [12]
12*6 =
72
Answer Link
ayepizzarolls
ayepizzarolls
01-11-2015
6((4*(72-63)/3))
6((4*9/3))
6((36/3))
6((12))
72
Answer Link
VER TODAS LAS RESPUESTAS ( 36+ )
Otras preguntas
Anderson was feeling sluggish after school and decided to drink an energy drink so he could focus on his homework. it didn't seem to help, so he drank another.
Solve the quadratic equation 2x^2 + 6 = 8x by graphing. A) x = –3, x = 1 B) x = –3, x = –1 C) x = –1, x = 3 D) x = 1, x = 3
why is the density of population low in karnali province?
At night, Brooks, age 4, is afraid of the sound of the train whistle and of going to bed without a light on. His excessive fears are an expression of:
how mnay layers are in a earth
Calculating the volume of an irregular solid
ABC DEF. The area of ABC is given. Find the area of DEF
Please select the word from the list that best fits the definition term used by geologists for water that soaks into the ground, fills the openings in the soil,
Convert 65,000,000 to scientific notation
What does derealization mean? What are the symptoms of it?Weirdcore edition please.